Systematic review and usability evaluation of writing mobile apps for children. Issue 3 (3rd July 2019) - Missen, Malik M. Saad; Javed, Amna; Asmat, Hina; Nosheen, Mariam; Coustaty, Mickaël; Salamat, Nadeem; Prasath, V. B. Surya
ABSTRACT: Writing apps for children have been developed in recent year to support effective learning and writing skills of students. In this work, we perform a systematic review of all currently available apps for the operating system iOS and Android. We consider a number of newly release children writing apps by focusing on their features like the range of functions, target user groups, operating language, acquisition costs, user ratings and the connection between acquisition cost and user ratings. In total, we analysed 497 apps based on functions offered and their cost to users. In addition to the systematic review of apps, we also perform a participant-based usability evaluation of a representative sample i.e. 8% sample of the total collected apps. Totally 40 apps are selected for usability evaluation including 20 apps for iOS and the remaining 20 apps for Android. As a result of usability evaluation of apps, it is found out that with the increase in the number of functions in a mobile app, the usability of the app decreases. The subjective evaluation reveals that participants felt better user experience with iPhone in comparison to Android enabled devices.